2008
DOI: 10.1038/sj.jid.5700948
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin 3 Induces Skin Pigmentation in a Keratin-Driven Inducible Mouse Model

Abstract: Endothelin 3 (Edn3) encodes a ligand important to developing neural crest cells and is allelic to the spontaneous mouse mutation occurring at the lethal spotting (ls) locus. Edn3(ls/ls) mutants exhibit a spotted phenotype due to reduced numbers of neural crest-derived melanocyte precursors in the skin. In this study, we show that when Edn3 is driven by the keratin 5 promoter and thereby placed proximal to melanocyte lineage cells, adult mice manifest pigmented skin harboring dermal melanocytes. Using a tetracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 70 publications
5
62
0
Order By: Relevance
“…Numerous in vitro studies using quail and mouse embryos have reported that EDN3 affects the melanocyte lineage population by increasing their number in a dose-dependent manner (Lahav et al 1996(Lahav et al , 1998Reid et al 1996;Opdecamp et al 1998;Dupin et al 2000). In addition, exogenous overexpression of EDN3 driven by keratin 5 in transgenic mouse embryos induced proliferation of melanocyte precursors and led to hyperpigmentation on most areas of their skin (Garcia et al 2008). Here, the highlevel expression of EDN3 mRNA in Silky chickens was detected at stage 18, and we obtained the same result at stages 15 and 24 (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous in vitro studies using quail and mouse embryos have reported that EDN3 affects the melanocyte lineage population by increasing their number in a dose-dependent manner (Lahav et al 1996(Lahav et al , 1998Reid et al 1996;Opdecamp et al 1998;Dupin et al 2000). In addition, exogenous overexpression of EDN3 driven by keratin 5 in transgenic mouse embryos induced proliferation of melanocyte precursors and led to hyperpigmentation on most areas of their skin (Garcia et al 2008). Here, the highlevel expression of EDN3 mRNA in Silky chickens was detected at stage 18, and we obtained the same result at stages 15 and 24 (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Corin, a transmembrane protease expressed by the DP, modifies the length of the yellow band by partially opposing Asip activity (Enshell-Seijffers et al 2008). Edn3 signaling can also promote the production of eumelanin over pheomelanin (Garcia et al 2008). Changes in Corin and Agouti activity are linked to significant changes in pigmentation of wild mouse populations (Manceau et al 2010(Manceau et al , 2011Linnen et al 2013), while preferential Edn3 activity has been implicated in the darker pigmentation of spots and stripes in the cat family (Kaelin et al 2013).…”
Section: Dp and Hair Pigmentationmentioning
confidence: 99%
“…The other genes in the first duplication, namely SLMO2, ATP5e and TUBB1, also showed increased expression. We do not know if these genes are involved in the FM phenotype, but EDN3 duplication may be a primary reason for dermal hyperpigmentation in FM chickens because a similar observation has been reported in mouse [20]. Hyperpigmentation in chickens is influenced by both FM and ID (inhibitor of dermal melanin).…”
Section: Discussionmentioning
confidence: 98%
“…EDN3 has a mitogenic effect on melanocytes [26]. For example, ectopic EDN3 expression results in dermal hyperpigmentation in a transgenic mouse model [20]. In Silkie embryos, the spatial characteristics of melanoblast migration and the timing are very different compared to wild-type embryos [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation